2011
DOI: 10.1061/(asce)nh.1527-6996.0000029
|View full text |Cite
|
Sign up to set email alerts
|

Wood Frame Building Response to Rapid-Onset Flooding

Abstract: Floods are considered to be among of the deadliest, costliest and most common natural disasters. Rapid onset, catastrophic floods inundate the shore quickly and manifest as deep water with high velocities. The deep water and high velocities caused by these floods inflict great pressures and forces on the built and natural environments and pose a threat to human safety. Recent disasters such as Hurricane Katrina in the Southern United States and the Sumatra tsunami in the Indian Ocean have revealed that communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…* Buoyancy can cause a building to drift from its foundation. Previous studies have shown that buildings will float when the flood depth reaches approximately three quarters of the building height (Becker et al, 2010). 1 Where limited information specific to developing countries' building practices was available, information from non-developing countries has been included.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…* Buoyancy can cause a building to drift from its foundation. Previous studies have shown that buildings will float when the flood depth reaches approximately three quarters of the building height (Becker et al, 2010). 1 Where limited information specific to developing countries' building practices was available, information from non-developing countries has been included.…”
Section: Accepted Articlementioning
confidence: 99%
“… Buoyancy can cause a building to drift from its foundation. Previous studies have shown that buildings will float when the flood depth reaches approximately three‐quarters of the building height (Becker et al., 2010). …”
Section: Asynergies Of Building‐level Drr Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Distributed resistance parameters are needed for local prediction of velocity [10] [11] which might be required for damage assessment or predictions of sediment erosion and deposition [12]. Based on Becker et al [13] findings, he concluded that structural failure comprises a large portion of the response space for higher depth and velocity combination under flood response scenarios. Thus, by developing a greater understanding of building response to high-velocity floodwaters through this type of behavior modeling, actions could be investigated that may improve resistance of buildings in flood-prone areas.…”
Section: Building Response and Flood Damagementioning
confidence: 99%
“…Becker et al (2011) show that a key factor of building response to the external actions is the interaction between the structural components of the building and the wave. The pressure of the tsunami bore can be likened to the pressures attributable to winds that are treated as uniform lateral pressures acting along the entire height of the building.…”
Section: Introductionmentioning
confidence: 99%